Análise da imparcialidade nas decisões colegiadas do contencioso administrativo tributário do estado do Ceará 2012 a 2016 - Bandeira, Cássio Rodrigo Vasconcelos (2019)
The objective of this paper was to analyze the votes of the judges classists and state officials of the second instance judgments in the Ceará’s Administrative Council Tax Councils. The importance of the theme s to the extent that impartiality and independence should prevail in the counselors' judgment. Thus, counselors must abstract whether they represent civil entities or the taxing institution, and construct their judgment solely and exclusively based on correct law enforcement. So, a qualitative Logit response model was estimated. It was expected to know the factors that lead to this favorable vote of the judge and the contribution of each of them in the conception of individual judgments that maintain at least half of the value originally launched in the assessment. The importance of the rapporteur's favorable vote on the probability of favorable votes of the other judges was evidenced.